Reinterpretasi Mazmur 23 sebagai Teks Quantum Affirmasi Healing - Yudhi Kawangung; Nelci Nafalia Ndolu; Munatar Kause (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2020)
This article aims to reinterpret the text of Psalm 23 through the lens of the human energy center (chakra) healing therapy. The text of Psalm 23 is studied using the text analysis method. The findings are formulated using the lens of the quantum affirmation theory. The results showed that the text of Psalms 23 is a prayer Psalms that become affirmative sentences, which are able to renew the negative energy in the human chakra and restore the normal colors of the body chakra aura so that humans can think, work optimally and achieve life success. Psalm 23 as a quantum affirmation of David in achieving success can be used as a form of therapy to cleanse the aura of everyone, especially for church leaders to always emit a positive aura and reach a successful ministry. Abstrak Artikel ini bertujuan untuk mereinterpretasi teks Mazmur 23 dalam lensa terapi penyembuhan pusat energi (cakra) manusia. Teks Mazmur 23 dikaji menggunakan metode analisis teks. Temuan dirumuskan dengan menggunakan lensa teori Quantum affirmasi. Hasil penelitian menunjukkan bahwa teks Maz-mur 23 merupakan Mazmur doa yang menjadi kalimat-kalimat afirmasi, yang mampu membaharui energi negatif dalam cakra manusia dan memulihkan war-na normal aura cakra tubuh, sehingga manusia dapat berpikir, berkarya dengan maksimal dan mencapai kesuksesan hidup. Mazmur 23 sebagai quantum affir-masi Daud dalam meraih sukses dapat digunakan sebagai bentuk terapi mem-bersihkan aura setiap orang khususnya bagi pemimpin gereja agar selalu memancarkan aura positif dan menggapai pelayanan yang sukses